2010
DOI: 10.1016/j.jasms.2010.03.047
|View full text |Cite
|
Sign up to set email alerts
|

‘Fixed charge’ chemical derivatization and data dependant multistage tandem mass spectrometry for mapping protein surface residue accessibility

Abstract: Protein surface accessible residues play an important role in protein folding, protein-protein interactions and protein-ligand binding. However, a common problem associated with the use of selective chemical labeling methods for mapping protein solvent accessible residues is that when a complicated peptide mixture resulting from a large protein or protein complex is analyzed, the modified peptides may be difficult to identify and characterize amongst the largely unmodified peptide population (i.e., the 'needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…For CID-MS/MS and -MS 3 analysis of the digests from native or oxidized DMBNHS-modified CN, the mass spectrometer was operated in a DDCNL mode by performing CID-MS/MS scans on the five most intense ions from each MS survey scan, while simultaneously searching for defined neutral losses (within an m / z variance of ±0.5) corresponding to single, double, and triple S(CH 3 ) 2 neutral losses from [M N + + (m- N )H] m + precursor ions, where M represents the peptide, N represents the number of modifications, and m represents different charge states ranging from +2 to +5 (see Supplemental Table S1, Supporting Information). 31 If a predefined neutral loss was detected above a threshold abundance of 1.0 × 10 4 counts, CID-MS 3 was automatically initiated to isolate then further dissociate the most intense neutral loss product ion. For targeted ETD-MS/MS analysis of digests from native or oxidized DMBNHS-modified CN, the mass spectrometer was operated in a data-dependent mode where only predefined precursor ions of interest observed within a ± 0.5 min elution window determined from previous HPLC-ESI-MS, CID-MS/MS, and -MS 3 experiments, were selected for dissociation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For CID-MS/MS and -MS 3 analysis of the digests from native or oxidized DMBNHS-modified CN, the mass spectrometer was operated in a DDCNL mode by performing CID-MS/MS scans on the five most intense ions from each MS survey scan, while simultaneously searching for defined neutral losses (within an m / z variance of ±0.5) corresponding to single, double, and triple S(CH 3 ) 2 neutral losses from [M N + + (m- N )H] m + precursor ions, where M represents the peptide, N represents the number of modifications, and m represents different charge states ranging from +2 to +5 (see Supplemental Table S1, Supporting Information). 31 If a predefined neutral loss was detected above a threshold abundance of 1.0 × 10 4 counts, CID-MS 3 was automatically initiated to isolate then further dissociate the most intense neutral loss product ion. For targeted ETD-MS/MS analysis of digests from native or oxidized DMBNHS-modified CN, the mass spectrometer was operated in a data-dependent mode where only predefined precursor ions of interest observed within a ± 0.5 min elution window determined from previous HPLC-ESI-MS, CID-MS/MS, and -MS 3 experiments, were selected for dissociation.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported the development of a strategy for mapping solvent-accessible lysine residues within proteins, via covalent labeling with a novel amine-specific protein modification reagent, S , S ′-dimethylthiobutanoylhydroxysuccinimide ester (DMBNHS), and its application to a model protein, namely, human cellular retinoic acid binding protein II. 31 After reaction at different reagent to protein ratios, followed by protein digestion, capillary HPLC-ESI-MS and automated collision-induced dissociation–tandem mass spectrometry (CID-MS/MS) in an ion trap mass spectrometer, the modified peptides, and the number of modifications within each peptide, were readily identified via the dominant characteristic neutral loss(es) of a dimethylsulfide moiety from the modified lysine amino acid side chain. 31,32 The observation of the neutral losses were then used to automatically trigger the acquisition of a “data-dependent neutral loss mode” MS 3 spectrum for peptide sequence and modification site(s) characterization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various labels can be utilized, including amino acid side chain-specific labeling reagents such as iodoacetamide (cysteines), N-bromosuccinimide (tryptophan), diethylpyrocarbonate (carboxyl acids), and S,S 1 -dimethylthiobutanoy lhdroxysuccinimide (lysines). [14][15][16][17] Structural information from these reagents may not be as comprehensive due to their inherent specificities.…”
Section: Structural Analysis Of a Therapeutic Monoclonal Antibody Dimmentioning
confidence: 99%
“…We have previously reported that peptides containing ‘fixed charge’ dialkylsulfonium ion derivatives located on selected functional groups of certain amino acids, including the thioether side chain of methionine (formed by reaction with phenacylbromide under acidic conditions) [56-58], the thiol side chain of cysteine (formed by reaction with 3-([ N -bromoacetamido]propyl)-methylphenacylsulfonium bromide (BAPMPS)) [59], or the amino side chain of lysine or peptide N-termini (formed by reaction with S,S ′-dimethylth-iobutanoylhydroxysuccinimide ester (DMBNHS)) [60] all undergo the exclusive neutral loss(es) of dialkylsulfide groups upon CID-MS/MS, independently of the amino acid composition and precursor ion charge state (i.e. ; proton mobility), thereby enabling the selective identification of derivatized peptides from within complex mixtures.…”
Section: Introductionmentioning
confidence: 99%